Self-etching adhesive systems, bond strength and nanofiltration: a review - Parra-Lozada, Maritza; Garzón-Rayo, Herney (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Self-etching adhesive systems have greatly enhanced clinical procedures as they have allowed not only developing components and their functions but also reducing application times. During the latest decade they have been subjected to permanent clinical and experimental tests in order to assess their performance. Their multiple advantages contrast to their low effectiveness in terms of bond strength and permeability, as water drops develop on the adhesive interface, thus favoring nanofiltration. As self-etching adhesive systems offer lower reliability in relation to bond strength and nanofiltration in comparison to adhesives of fourth and fifth generation, the latter stand as the golden standard for comparative studies, as they keep using the acid etching protocol, by means of 35 or 37% ortophosphoric acid. The goal of this review article is to present the evolution of self-etching adhesive systems and to discuss bond strength and nanofiltration as variables that intervene in their poor performance, providing dentists with the fundamentals for a critical accurate selection of etching systems.